A new species of Branchinecta (Crustacea: Anostraca) from Uruguay - Rogers, D. Christopher; Lorenz, Helen Racz (Zootaxa, 2015)
Branchinecta uruguayensis, a new species of fairy shrimp, is described from a single seasonally astatic aquatic habitat in coastal Uruguay. This is the first record of an anostracan from the nation of Uruguay. Male B. uruguayensis n. sp. are separated from other Branchinecta species by the form of the second antennae. Branchinecta uruguayensis n. sp. share the distal antennomere lobiform projection with B. papillata Rogers, De los Rios, & Zúñiga, 2008 and B. achalensis César, 1985. Branchinecta uruguayensis n. sp. females are readily separated from all other Branchinecta by the presence of posteriolateral thoracic spines and lateral crenulations on the first abdomen segment margins. A key is provided to the Branchinectidae of South America.